Physical Therapy Intervention for Individuals with Rett Syndrome - Meir Lotan; Susan Hanks (The Scientific World Journal)
Individuals with Rett syndrome (RS) present a vast array of orthopedic and neurological difficulties. Typical problems, which may need to be addressed, when treating this population are functional limitations, low cardiovascular capacity, hypotonia, ataxia, apraxia, loss of transitional movements, spasticity, scoliosis and/or kyphosis, loss of ambulation, loss of hand function, foot deformities, and spatial disorientation. Coping with such difficulties and overcoming the associated limitations carry a wearisome task for the individual with Rett as well as for her family. An informed and intensely applied physical therapy regime can help the child and the family cope and even overcome the above-mentioned limitations. The present article presents some insights regarding the intervention with individuals with RS, an overview of typical neuromuscular problems associated with RS, and appropriate suggestions pertaining to clinical intervention that have been found to contribute to this populations well-being. The information presented is mainly based on the clinical knowledge of the authors.